IL-21 is required for the maintenance and pathogenesis of murine Vγ4+ IL-17-producing γδT cells - Ishikawa, Junichi; Suto, Akira; Abe, Kazuya; Hayashi, Yuki; Suga, Kensuke; Tanaka, Shigeru; Kageyama, Takahiro; Iwata, Arifumi; Suzuki, Kazumasa; Suzuki, Kotaro; Nakajima, Hiroshi (Frontiers in Immunology, 2023)
Murine IL-17-producing γδT (γδT17) cells are divided into two subsets: natural γδT17 (nγδT17) cells, whose development is restricted to the fetal thymus, and inducible γδT17 cells, which require antigen exposure for their IL-17 production and are presumed to develop from Rorc+ Il17a-CCR9+ immature γδT17 cells in the adult thymus and whose T cell receptor (TCR) is biased toward Vγ4. Although IL-23 is known to be involved in developing γδT17 cells, the roles of other cytokines, such as IL-21, which is involved in developing Th17 cells like IL-23, in the development, maintenance, and pathophysiology of γδT17 cells remain unknown. Here, we show that IL-21 is dispensable for the fetal thymic development of nγδT17 cells but is required for the peripheral maintenance of Vγ4+ nγδT17 cells. Upon stimulation with γδTCR, IL-1 plus IL-21 induces the proliferation of Vγ4+ nγδT17 cells via STAT3 as effectively as IL-1 plus IL-23. Using bone marrow chimeric mice, we demonstrated that immature γδT17 cells are produced de novo in the adult mice from donor adult bone marrow cells and that IL-21 is dispensable for their development. Instead, IL-21 is required to expand newly induced Vγ4+ γδT17 cells in the periphery upon immunization. Finally, using adoptive transfer experiments of γδT17 cells, we found that IL-21 receptors on γδT17 cells are involved in maintaining Vγ4+ γδT17 cells, subsequent infiltration of Th17 cells into the spinal cord, and exacerbation of experimental autoimmune encephalomyelitis. Collectively, IL-21 plays a vital role in the maintenance and pathogenesis of Vγ4+ γδT17 cells.